Basic Phytotherapy and Podiatry - Palomo López, Patricia; Revuelta García, Enrique (Revista Internacional de Ciencias Podológicas, 2011)
This work tries to offer a series of knowledge or basic premises on the fitotherapy and as its use can help us in chiropody. We present a series of conclusions on the medicinal plants and their pharmacology, as well as the most important active elements, the groups in that is divided…Despite, we speak of the fundamental realities of the fitotherapy without despising the traditional medicine, and by all means, also we speak of the disadvantages that it has. We try to apply the fitotherapy to the chiropody, showing here a small, minimum series of medicinal plants that can come in useful, a form of small compendium that shows its properties to us. Then, we applied these knowledges to certain very frequent pathologies in the foot, as the disease in the smaller bones of the ffetgout-, the sprains-wrench or twist the ligaments of an ankle violently, warts- small bening qrowth on the skin. And to finalize, some domestic remedies and the conclusions.